2019
DOI: 10.1186/s43042-019-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum level and single-nucleotide polymorphisms of toll-like receptor-7 among urinary bladder cancer Iraqi patients

Abstract: Background: Toll-like receptor 7 (TLR7), a member of TLR family, plays a pivotal role in pathogenesis of different malignancies. Among these is urinary bladder cancer (UBC), which has not been extensively studied. Therefore, it was aimed to determine TLR7 serum level in UBC patients and evaluate its association with some demographic and clinicopathological characteristics. In addition, four TLR7 single-nucleotide polymorphisms (SNPs: rs179018, rs179019, rs179020, and rs179021) were investigated to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The interaction between sex hormones, the environment, and genotype during individual development, as well as the fact that all cases were adult, are the two most plausible explanations for the female predominance in SLE. This finding is consistent with earlier research that showed that females are more likely than males to develop SLE after puberty due to elevated levels of circulating oestrogen (4,29). The regulating role of microRNAs in the immune system occurs in a delicate tune.…”
Section: Micro-rna126 Polymorphismsupporting
confidence: 92%
See 1 more Smart Citation
“…The interaction between sex hormones, the environment, and genotype during individual development, as well as the fact that all cases were adult, are the two most plausible explanations for the female predominance in SLE. This finding is consistent with earlier research that showed that females are more likely than males to develop SLE after puberty due to elevated levels of circulating oestrogen (4,29). The regulating role of microRNAs in the immune system occurs in a delicate tune.…”
Section: Micro-rna126 Polymorphismsupporting
confidence: 92%
“…Hardy-Weinberg equilibrium. Most studies agree that SLE affects women more frequently than it does men, and the findings from the studies given show a risk effect for female sex and age in the aetiology of SLE (33,28,4). The interaction between sex hormones, the environment, and genotype during individual development, as well as the fact that all cases were adult, are the two most plausible explanations for the female predominance in SLE.…”
Section: Micro-rna126 Polymorphismmentioning
confidence: 83%
“…An Iraqi study from Urology Clinic of Baghdad Teaching Hospital in 2019 included 66 patients with TCC with the age ranging 24-90 years. Male percentage was 89.4% 59 while for females it was 10.6% [18].…”
Section: Discussionmentioning
confidence: 87%
“…So the twentieth decade of age is considered a crucial risk factor for SLE exception before puberty age [22]. The female gender is an additional risk factor, and most studies agree that SLE occurs more frequently in women than in men [23][24][25]. Two important explanations may justify the female-gender dominancy in SLE; the interaction between the environment, genotype, and sex hormones during individual development, and all cases were adult and this is similar to previous research clarified, that females with SLE have a higher prevalence than males after puberty age due to high levels of circulating estrogen [25,26].…”
Section: Resultsmentioning
confidence: 99%